Іммобілізація хітозану на поверхні трекових мембран - Мурланова, Т.В.; Вакулюк, П.В.; Нижник, В.В. (Видавничий дім "Академперіодика" НАН України, 2008)
A method for the chitosan immobilization on the surface of track polyethyleneterephthalate membranes with a preliminary treatment of their surface by a water solution of sodium periodate is developed. The produced membranes have antibacterial characteristics stable in time.